The role of serum testosterone and dehydroepiandrosterone sulfate in kidney function and clinical outcomes in chronic kidney disease: a systematic review and meta-analysis. Issue 6 (23rd June 2022) - van der Burgh, Anna C; Khan, Samer R; Neggers, Sebastian J C M M; Hoorn, Ewout J; Chaker, Layal
Abstract : Objective/design: Testosterone might mediate sex differences in kidney function and chronic kidney disease (CKD). However, few studies analyzing the association between testosterone and kidney function showed conflicting results. Therefore, we performed a systematic review and meta-analysis. Methods: Six electronic databases were searched from inception to March 4, 2020, for studies that investigated the association of (i) testosterone status with kidney function in the general population or (ii) testosterone status with clinical outcomes (kidney function decline, kidney failure, cardiovascular (CV) events, and cardiovascular and all-cause mortality) in CKD patients. We used random and fixed-effect models to obtain pooled effect estimates with 95% confidence intervals (CIs). Results: No randomized–controlled trials that met the inclusion criteria were identified. One study was conducted in the general population and reported an increased risk of incident CKD with low vs normal testosterone (hazard ratio (HR): 1.38, 95% CI: 1.05;1.80). Seven studies were conducted in men with CKD and included testosterone as determinant, of which six could be meta-analyzed. Low testosterone was associated with an increased risk of all-cause mortality and CV events (pooled HR: 1.98, 95% CI: 1.36;2.89; pooled HR of 2.40, 95% CI: 1.22;4.71, respectively). Two studies showed an increased risk of all-cause mortality with decreased dehydroepiandrosterone sulfate (DHEAS) in men with CKD; results regarding CV events were conflicting. Conclusions: Although literature is scarce, evidence suggests that lower testosterone may increase CKD risk in the general population and risk of all-cause mortality and CV events in men with CKD. Whether testosterone supplementation could prevent these potential detrimental outcomes should be determined in future intervention studies.